PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PROGRAM LINIER DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - de HAAS, Ivone; Molle, Juliana Selvina; Ngilawajan, Darma Andreas (Jurnal Pendidikan Matematika (JUPITEK), 2020)
The purpose of this research is to improve students’ learning outcome on the topic liniear programing by using Problem Based Learning. This research is conducted in 11th grade students of senior high school 1 Saparua in academic year 2019/ 2020. Total number students on experiment grup is 25. This research took 2 cycles in order to achieve passing grade by most students. Every cycle consists of two class meeting. Data collected by using essay tests on each cycle and observation sheet. Further more, data analyzed by using qualitative nd quantitative analysis. The results show that students’ achievement on cycle I which reached passing grade is 56% of total number students. Meanwhile, students’ achievement which reached passing grade on cycle II is 80% of total number of students. There can be concluded that students’ learning outcome has improved 24% through Problem Based Learning